1988
DOI: 10.1017/s000335610000307x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intake by cattle from degradation characteristics of roughages

Abstract: Five different straws consisting of two varieties of winter barley, two varieties of spring barley and one variety of winter wheat were chosen due to differences in degradation characteristics determined by using nylon bags incubated in the rumen of cattle and describing the straw using the equation: p = a + b (1 – e–ct). To increase variation in degradability, batches of the same straws were also treated with anhydrous ammonia in a sealed oven.The straws were subsequently offered ad libitum to groups of steer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
11

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(45 citation statements)
references
References 6 publications
1
33
0
11
Order By: Relevance
“…Since the cell-wall carbohydrates are the most important components of the straws, an efficient microbial digestion in the rumen is crucial for their utilization in ruminant feeding. In recent years, a number of studies have suggested that degradation characteristics of these types of feeds in the rumen will provide a useful basis for the evaluation of their nutritive value [13] …”
Section: Introductionmentioning
confidence: 99%
“…Since the cell-wall carbohydrates are the most important components of the straws, an efficient microbial digestion in the rumen is crucial for their utilization in ruminant feeding. In recent years, a number of studies have suggested that degradation characteristics of these types of feeds in the rumen will provide a useful basis for the evaluation of their nutritive value [13] …”
Section: Introductionmentioning
confidence: 99%
“…These models are state-specific and thus only valid under similar circumstances under which they have been developed. Some of these models rely entirely on animal characteristics (ARC, 1980) while others are based on feed properties such as degradability (Ørskov et al, 1988;Blumel & Ørskov, 1993;Kibon & Ørskov, 1993) or on urinary excretion products (Nsahlai et al, 2002). Since the relationship between roughage intake and degradability is a positive one, this only strengthens the view that roughage intake by ruminant animals is limited by rumen (gut) "fill".…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se ainda que outras características da forragem possam ter influenciado a predição da ingestão, como a taxa de redução de partículas maiores, o tempo de colonização destas, assim como a taxa constante de saída de digesta ruminal (∅RSKOV et al, 1988) e que não estão presentes como variáveis nestas equações.…”
Section: Resultsunclassified